THE IMPROVEMENT OF STUDENT'S MATHEMATICAL COMMUNICATION ABILITY BY USING COOPERATIVE LEARNING: COURSE REVIEW HORAY - Leni Agustina Daulay; Hilda Hakim; Lindi Dewi Sartikawati (UIN Sumatera Utara Medan, 2019)
This research was conducted to look at the increase in mathematical communication towards cooperative learning type Course Review Horay assisted PowerPoint in the seventh grade of  SMP Negeri 1 Takengon. This research used Experiment Research with Quantitative research. SMP Negeri 1 Takengon was the population of research. Two classes were determined by purposive random sampling for the sample of research, called experimental class and control class. The experimental class was taught by using a cooperative learning type Course Review Horay assisted PowerPoint while the control class was taught by STAD. The conclusion was that by using a learning model Course Review Horay, the students more active because it can be suggested with the peers and its language. Things can improve the ability of mathematical communication students. Along with the development of their understanding of the material has been taught students to do math activities that encourage the application of mathematical communication ability.